Preparation method of self-decomposition composite catalyst and application of self-decomposition composite catalyst to construction of photoelectrochemical cell in ammonia production
By using the self-decomposed composite catalyst CuCo2O4/CuO in photoelectrochemical cells, nitrates are reduced to ammonia, which solves the energy consumption and pollution problems of traditional ammonia production processes, and achieves efficient and environmentally friendly ammonia production.
Patent Information
- Application Number
- CN202411413800.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-28
AI Technical Summary
The existing ammonia production process consumes a large amount of fossil energy, resulting in greenhouse gas emissions, and the problem of nitrate pollution has not been effectively solved.
Using a self-decomposed composite catalyst CuCo2O4/CuO, the nitrate is reduced to ammonia through photoelectrochemical cells, achieving green and sustainable production of ammonia.
This method achieves efficient ammonia production under mild reaction conditions, with excellent selectivity and stability, with a Faraday efficiency up to 88.9% and a conversion rate of up to 77.4%.
Smart Images

Figure CN119530860A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoelectrocatalytic ammonia synthesis catalysts, and specifically relates to a method for preparing a self-decomposing composite catalyst and an application of the composite catalyst in constructing a photoelectrochemical cell in ammonia production. Background Art
[0002] Ammonia (NH3) is one of the world's most produced chemicals and is considered a promising hydrogen energy storage medium and a carrier for global renewable energy transportation. Currently, the energy-intensive Haber-Bosch ammonia process is the dominant route for large-scale industrial ammonia synthesis, which consumes a large amount of fossil energy and causes greenhouse gas emissions. At the same time, nitrates are widely distributed in industrial wastewater, nuclear wastewater and contaminated groundwater, and may be converted into harmful nitrites (NO2 - ), which requires urgent treatment.
[0003] Under mild reaction conditions, waste NO3 is converted to - The conversion into valuable NH3 would not only solve the nitrate and / or nitrite pollution problem, but also establish a green and sustainable route for the conventional Haber-Bosch ammonia production process. Summary of the invention
[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a self-decomposing composite catalyst to construct a photoelectrochemical cell to achieve ammonia production.
[0005] The technical solution adopted by the present invention is:
[0006] A method for preparing a self-decomposing CuCo2O4 / CuO composite catalyst comprises the following steps:
[0007] 1) Cu(CH3COO)·2H2O, Co(CH3COO)2·4H2O and CO(NH2)2 were added into a beaker filled with deionized water and dissolved under strong magnetic stirring to form a homogeneous solution; the above solution and the pretreated Ti mesh were placed into an autoclave, and then the autoclave was sealed for hydrothermal reaction;
[0008] 2) The integrated electrode obtained in the autoclave was rinsed with deionized water and dried at 60°C overnight;
[0009] 3) Calcine the integrated electrode to obtain a black CuCo2O4 / CuO-loaded integrated electrode.
[0010] Furthermore, in the above-mentioned preparation method, in step 1), the pretreatment method of the Ti mesh is: cutting the Ti mesh into 2cm×2cm size, grinding off the surface oxide with sandpaper, then heating it in 10% oxalic acid solution, and washing it with deionized water under ultrasonic conditions until it is neutral.
[0011] Furthermore, in the above preparation method, in step 1), the molar ratio of Cu(CH3COO)·2H2O, Co(CH3COO)2·4H2O and CO(NH2)2 is 1:2:5.
[0012] Furthermore, in the above preparation method, in step 1), the hydrothermal reaction condition is 120° C. for 6 hours.
[0013] Furthermore, in the above preparation method, in step 3), the calcination conditions are: calcination at 450° C. in air for 2 h, and a heating rate of 5° C. / min.
[0014] The CuCo2O4 / CuO integrated electrode obtained by any of the preparation methods described above is used to construct a photoelectrochemical cell for the application in photoelectrocatalytic nitrate reduction to produce ammonia.
[0015] Furthermore, the above-mentioned application is carried out as follows: a three-electrode system is used for photoelectrocatalytic nitrate reduction to produce ammonia, wherein a CuCo2O4 / CuO integrated electrode is used as a working electrode and Ag / AgCl is used as a reference electrode, which are located in the cathode chamber of an H-type electrolytic cell, and a Pt sheet is used as a counter electrode and is located in the anode chamber of an H-type electrolytic cell, 20 mL of 0.5 M Na2SO4 containing 0.05 M NaNO3 is added to each of the two chambers as an electrolyte, and a 300 W xenon lamp provides visible light irradiation, λ>420 nm; before electrolysis, high-purity argon gas is passed into the electrolyte for 30 minutes to remove impurity gases in the electrolyte.
[0016] Furthermore, for the above application, the voltage is set to -0.8 to -1.6 V vs RHE.
[0017] Furthermore, in the above application, the electrolysis is continued for 1 hour.
[0018] The beneficial effects of the present invention are:
[0019] 1. The present invention utilizes the unique self-decomposition property of materials to construct semiconductor heterojunctions and prepare self-decomposing spherical CuCo2O4 / CuO catalysts loaded on integrated electrodes, which have large specific surface areas and are beneficial to material transport and electron transfer during the reaction process. The construction of heterojunctions can effectively enhance the separation of photoelectron-hole pairs, thereby having better light absorption and faster charge transfer. The strong interaction between the decomposed CuO and CuCo2O4 regulates the electronic structure of the catalyst, which is beneficial to NO3 -The adsorption of CuCo2O4 / CuO can inhibit the side reaction of hydrogen evolution and improve the selectivity of ammonia production. Therefore, this spherical CuCo2O4 / CuO catalyst shows excellent performance in the process of photoelectrocatalytic nitrate reduction to produce ammonia: in an electrolyte containing 50mM NaNO3, the CuCo2O4 / CuO integrated electrode reaches 30.5mM / h at -1.2V vs RHE, with a maximum Faraday efficiency of 88.9% and a conversion rate of 77.4%.
[0020] 2. The CuCo2O4 / CuO integrated electrode prepared by the present invention can utilize environmentally friendly renewable energy to realize the value-added process of chemicals from pollutant nitrates, which is an environmentally friendly production strategy that achieves multiple goals at one stroke. The self-decomposing spherical CuCo2O4 / CuO catalyst has high activity, high selectivity and excellent stability, and has excellent development prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 X-ray diffraction (XRD) patterns of CuCo2O4 / CuO prepared in Example 1, CuCo2O4 prepared in Comparative Example 1, and CuO catalysts prepared in Comparative Example 2.
[0022] Figure 2 Scanning electron microscope (SEM) images of CuCo2O4 (a) prepared in Comparative Example 1 and CuCo2O4 / CuO (b) prepared in Example 1.
[0023] Figure 3 SEM image of the CuCo2O4 / CuO catalyst prepared in Example 1 and the corresponding energy dispersive X-ray (EDX) element distribution map.
[0024] Figure 4 X-ray photoelectron spectra (XPS) of the CuCo2O4 / CuO prepared in Example 1, the CuCo2O4 prepared in Comparative Example 1, and the CuO catalyst prepared in Comparative Example 2, wherein a shows the full spectrum, which proves the presence of elements C, O, Co and Cu, b is the high-resolution spectrum of the Cu 2p energy level, c is the high-resolution spectrum of the Co 2p energy level, and d is the high-resolution spectrum of the O1s energy level.
[0025] Figure 5 This is the standard curve for determining NH3 content using an ammonia gas sensitive electrode.
[0026] Figure 6 This is the change diagram of NH3 production and Faraday efficiency corresponding to the potential optimization process of nitrate reduction process.
[0027] Figure 7These are transient photocurrent diagrams of CuCo2O4 / CuO prepared in Example 1, CuCo2O4 prepared in Comparative Example 1, and CuO prepared in Comparative Example 2.
[0028] Figure 8 These are the electrochemical impedance spectroscopy (EIS) graphs of the CuCo2O4 / CuO prepared in Example 1, the CuCo2O4 prepared in Comparative Example 1, and the CuO catalysts prepared in Comparative Example 2.
[0029] Fig. 9 Steady-state photoluminescence (PL) spectra of the CuCo2O4 / CuO prepared in Example 1, the CuCo2O4 prepared in Comparative Example 1, and the CuO catalysts prepared in Comparative Example 2.
[0030] Fig.10 This is the cycle performance diagram of the CuCo2O4 / CuO catalyst prepared in Example 1. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments and drawings. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The embodiments listed below are only for further understanding and implementation of the technical solution of the present invention, and do not constitute further limitation of the claims of the present invention. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] 1) Pretreatment of Ti mesh: The Ti mesh was cut into 2 cm×2 cm size, the surface oxide was polished off with sandpaper, and then heated in 10% oxalic acid solution and washed with deionized water under ultrasonic conditions until neutral.
[0034] 2) Synthesis of CuCo2O4 / CuO integrated electrode by simple hydrothermal reaction: Dissolve Cu(CH3COO)·2H2O (1mmol), Co(CH3COO)2·4H2O (2mmol) and CO(NH2)2 (5mmol) in 40mL deionized water and dissolve under strong magnetic stirring to form a uniform solution. The above solution and the pretreated Ti mesh were placed in a 100mL autoclave and treated in an oven at 120℃ for 6h. After the reaction was completed, it was naturally cooled to room temperature, and the integrated electrode was taken out and rinsed with deionized water several times, and dried at 60℃. Finally, it was calcined in air at 450℃ for 2 hours in a muffle furnace (heating at 5℃ / min) to obtain a CuCo2O4 / CuO integrated electrode.
[0035] Comparative Example 1
[0036] We synthesized the CuCo2O4 integrated electrode using a method and procedure similar to that of Example 1. The difference from Example 1 is that only the calcination temperature was changed to 300°C, that is, the integrated electrode obtained by the hydrothermal method was calcined at 300°C for 2h to convert the supported catalyst precursor into CuCo2O4, thereby obtaining a CuCo2O4 integrated electrode.
[0037] Comparative Example 2
[0038] For the synthesis of the CuO integrated electrode, compared with Example 1, Co(CH3COO)2·4H2O was not added, and all other processes were the same as the preparation process of the CuCo2O4 / CuO integrated electrode.
[0039] Results Analysis
[0040] The CuCo2O4 / CuO catalyst in Example 1 was characterized by X-ray diffraction. Figure 1 It can be observed that the XRD pattern of CuCo2O4 / CuO shows the coexistence of characteristic diffraction peaks of CuCo2O4 and CuO. The X-ray diffraction (XRD) pattern proves the successful synthesis of the catalyst.
[0041] The CuCo2O4 / CuO catalyst prepared in Example 1 and the CuCo2O4 catalyst prepared in Comparative Example 1 were characterized by scanning electron microscopy. Figure 2 As shown in a, in Comparative Example 1, the synthesized CuCo2O4 presents a spherical shape. However, the CuCo2O4 / CuO catalyst of Example 1 presents a 3D spherical morphology ( Figure 2 b), where the diameter is about 5 μm, which may be due to the gradual roughening of the surface caused by its own decomposition. The rough surface is conducive to the mass transfer process between the catalyst and the electrolyte solution.
[0042] The EDX elemental analysis image of the CuCo2O4 / CuO catalyst prepared in Example 1 is as follows: Figure 3 It shows that O, Co and Cu elements are uniformly distributed in the CuCo2O4 / CuO heterostructure without obvious interface.
[0043] The CuCo2O4 / CuO catalyst was analyzed by X-ray photoelectron spectroscopy. Figure 4 shown. Figure 4The X-ray photoelectron spectroscopy of Example 1 is compared with that of Comparative Examples 1 and 2. The results show that the presence of CuO in the catalyst modulates the electronic structure of CuCo2O4 / CuO. Compared with pure CuCo2O4 and CuO, the binding energy of Cu and Co in CuCo2O4 / CuO shifts. These shifts indicate changes in the electron density around atoms and strong electronic interactions during the electron transfer from CuO to CuCo2O4 in the CuCo2O4 / CuO heterojunction, which is conducive to the establishment of a z-type heterojunction.
[0044] Example 2
[0045] The electrocatalytic nitrate reduction reaction was tested using a three-electrode system with the support of the Chi660e electrochemical workstation. The cathode ammonia production rate under the three-electrode structure was studied using a CuCo2O4 / CuO integrated electrode as the cathode, an Ag / AgCl reference electrode and a platinum counter electrode. The reaction was carried out in 20mL of 0.5M Na2SO4 solution (containing 0.05M NaNO3), and a 300W xenon lamp provided visible light irradiation (λ>420nm). Before the test, high-purity argon gas was passed into the electrolyte for 30 minutes to remove impurity gases in the electrolyte. The test was carried out using the chronopotentiometry method, with the voltage set to -1.2V vs RHE. After 1 hour of continuous electrolysis, the electrolyte in the cathode chamber was collected. An ammonia-sensitive electrode was used to test the NH4 + concentration and calculate the corresponding ammonia yield and Faradaic efficiency.
[0046] Example 3
[0047] Soak the ammonia gas sensitive electrode in deionized water, and when the reading is stable above 80mV, the measurement can be started. Take 0.5mL of the electrolyte solution in Example 2, dilute to 10mL, add 0.2mL of 10M NaOH solution, put in the electrode, and measure the solution potential mV1.
[0048] Since the solution potential is related to the ambient temperature, the standard curve was calibrated. Using the same method as in Example 3, 10 mL of 1 mM NH4Cl standard solution was added to the NaOH solution, and then the electrode was placed to record the reading mV2 and calibrate the standard curve. The NH4 in the electrolyte was calculated based on the calibrated standard curve. + concentration, the corresponding ammonia yield and Faraday efficiency can be further calculated. The standard curve is as follows: Figure 5 shown.
[0049] The integrated electrode prepared in Example 1 was used to construct a photoelectrochemical cell. When the photoelectrocatalytic nitrate reduction reaction was used to synthesize ammonia, the ammonia yield and Faraday efficiency were as follows: Figure 6 As shown, the optimal voltage condition is screened out as the result when the working voltage is -1.2VVs.RHE.
[0050] Example 4
[0051] The catalysts synthesized in Example 1 and Comparative Examples 1-2 were used to test the carrier separation efficiency. The test was to measure the transient photocurrent response and electrochemical impedance spectrum Nyquist plot of three catalysts CuCo2O4 / CuO, CuCo2O4 and CuO. Figure 7 As shown in Figure 2, CuCo2O4 / CuO exhibits a higher photocurrent response, indicating that the heterojunction constructed between CuCo2O4 and copper oxide can suppress the e - -h+ pairs, thereby improving the photocurrent response. Figure 8 , the charge transfer characteristics of the three catalysts were studied by electrochemical impedance spectroscopy (EIS). Since the diameters of the semicircles of CuCo2O4, copper oxide and CuCo2O4 / CuO decrease in turn, the measurement results show that the CuCo2O4 / CuO photocathode promotes the transfer of interfacial charges to a great extent, leading to the effective utilization of photogenerated electrons.
[0052] Example 5
[0053] The catalysts synthesized in Example 1 and Comparative Examples 1-2 were characterized by steady-state photoluminescence (PL) spectroscopy to analyze the photodynamics of carriers. Fig. 9 The PL intensity of CuCo2O4 / CuO is much lower than that of CuCo2O4 and copper oxide, which means that the photoexcited charge complexation at the CuCo2O4 and CuO heterojunction interface is suppressed.
[0054] Example 6
[0055] The CuCo2O4 / CuO integrated electrode of Example 1 also has excellent cycle stability. We tested the cycle stability of the integrated electrode of Example 1 in a 0.5M Na2SO4 electrolyte containing 50mM nitrate at a potential of -1.2V vs. RHE. Fig.10 As shown, after 11 cycles, the catalyst still maintained a stable ammonia yield and Faraday efficiency. The above results prove that Example 1 has excellent cycle stability and has good development prospects.
Claims
1. A method for preparing a self-decomposing CuCo2O4 / CuO composite catalyst, characterized in that: The steps include: 1) Cu(CH3COO)·2H2O, Co(CH3COO)2·4H2O and CO(NH2)2 were added into a beaker filled with deionized water and dissolved under strong magnetic stirring to form a homogeneous solution; the above solution and the pretreated Ti mesh were placed into an autoclave, and then the autoclave was sealed for hydrothermal reaction; 2) The integrated electrode obtained in the autoclave was rinsed with deionized water and dried at 60°C overnight; 3) Calcine the integrated electrode to obtain a black CuCo2O4 / CuO-loaded integrated electrode.
2. The preparation method according to claim 1, characterized in that: In step 1), the pretreatment method of the Ti mesh is: cutting the Ti mesh into a size of 2 cm×2 cm, grinding off the surface oxide with sandpaper, then heating it in a 10% oxalic acid solution, and washing it with deionized water under ultrasonic conditions until it becomes neutral.
3. The preparation method according to claim 1, characterized in that: In step 1), the molar ratio of Cu(CH3COO)·2H2O, Co(CH3COO)2·4H2O and CO(NH2)2 is 1:2:
5.
4. The preparation method according to claim 1, characterized in that: In step 1), the hydrothermal reaction condition is 120° C. for 6 h.
5. The preparation method according to claim 1, characterized in that: In step 3), the calcination conditions are: calcination at 450° C. in air for 2 h, and a heating rate of 5° C. / min.
6. The CuCo2O4 / CuO integrated electrode obtained by the preparation method according to any one of claims 1 to 5 is used for constructing a photoelectrochemical cell for photoelectrocatalytic nitrate reduction to produce ammonia.
7. The use according to claim 6, characterized in that: The method is as follows: a three-electrode system is used for photoelectrocatalytic nitrate reduction to produce ammonia, wherein a CuCo2O4 / CuO integrated electrode is used as a working electrode and Ag / AgCl is used as a reference electrode, which are located in the cathode chamber of an H-type electrolytic cell; a Pt sheet is used as a counter electrode and is located in the anode chamber of an H-type electrolytic cell; 20 mL of 0.5 M Na2SO4 containing 0.05 M NaNO3 is added to each of the two chambers as an electrolyte; a 300 W xenon lamp provides visible light irradiation, with λ>420 nm; before electrolysis, high-purity argon gas is passed into the electrolyte for 30 minutes to remove impurity gases in the electrolyte.
8. The use according to claim 7, characterized in that: The voltage was set to -0.8 to -1.6 V vs RHE.
9. The use according to claim 7, characterized in that: The electrolysis was continued for 1 hour.
Citation Information
Cited By
Ti@TiO2 Array@Cu x Pt Alloy Composite Electrode and Its Preparation and Application in Photoelectrocatalytic Reduction of NO3 - to Ammonia
CN119980345B
Electroreduction nitrate ammonia synthesis CuOx / CoOx nano material with oxygen vacancy defect, and preparation method and application thereof
CN120231091A